Mental Health at the Workplace: Rights of Employees - Siti Hafsyah Idris; Ramesh Nair; Faizal Kurniawan (Human Rights in the Global South (HRGS), 2023)
In several ways, the Coronavirus Disease 2019 (COVID-19) pandemic has profoundly altered social and working environments. Social distancing policies, mandatory lockdowns, isolation periods, and the fear of becoming ill, in addition to the suspension of productive activity, loss of income, and fear of the future, all have an impact on citizens' and workers' mental health. Workplace factors can have a significant effect on whether people's mental health improves or deteriorates due to the pandemic. This article discusses Malaysian law's position on mental health and whether employers can be held liable for their employees' mental health. The goal of this article is to examine the legal aspects of workplace mental health issues. We conducted doctrinal research on existing laws and policies focusing on workers' rights issues related to mental health in the workplace during the pandemic. It is discovered that, anxiety, depression, post-traumatic stress disorder (PTSD), and sleep disorders are more likely to affect healthcare workers, particularly those on the frontlines, migrant workers, and workers in contact with the public. Job insecurity, long periods of isolation, and uncertainty about the future exacerbate the psychological condition, particularly among younger people and higher educational backgrounds. Therefore, numerous organisational and job-related interventions can help mitigate this scenario, but the regulatory mechanisms governing this matter must be clearly defined.